Tanggung Renteng Nasabah Matabaca pada Pembiayaan Qard{ul H{asan di KJKS Pilar Mandiri Surabaya - Chusnul Cholidah (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2016)
This 21st century constellation of the Indonesian economy is enlivened and colored by sharia economics. Starting from Islamic banks, Islamic rural banks, Islamic mutual funds, Sharia Multi-Level Marketing (Sharia MLM), and Islamic cooperatives. One of them is KJKS Pilar Mandiri Surabaya, which one of its activities is to help members regardless of the problem faced by members, especially the Abang Becak Ta'lim Assembly group (MATABACA), by providing loans without margins from KJKS Pilar Mandiri Surabaya with a contract scheme qard{ul h{asan. The implementation of joint responsibility of MATABACA customers in qard{ul h{asan financing at KJKS Pilar Mandiri Surabaya is done in groups, aimed at preventing bad loans. With the implementation of joint responsibility, if there are members who have not paid the installments will be immediately reminded by other joint responsibility members to pay. Because it can be penalized in the form of late fees. To increase the discipline of paying installments on joint responsibilities by reminding each other between group members before maturity, holding regular group meetings, and making group cash.